Implementation of Online Think Pairs Share (OTPS) Model to Improve Student Learning Outcome - Fitriyanti, Nurwulan; Zevika, Mona; Zakwandi, Rizki (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-ID JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><span style="font-size: 10.0pt; line-height: 107%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-ID; mso-bidi-language: AR-SA;" lang="EN-GB">This study was an online classroom action research (PTK) due to the COVID-19 pandemic. This study aimed to improve learning outcomes in calculus classes for physics engineering students using think pairs share. The online think pairs share (OTPS) learning model was optimized using the Learning Management System (LMS) platform in two learning cycles. The research sample was 46 students in the study program of physics engineering. The data were obtained from the pre-test-post-test scores, group discussions, and individual presentations. The results showed that the pre-test and post-test scores in cycle I were 37.16 and 68.41, while in cycle II, 41.20 and 68.65, respectively. In addition, the daily student score from the group discussion and individual presentation was 60.68 for the cycle I and 60.15 for cycle II. Furthermore, inferential analysis using the Kolmogorov-Smirnov test proves that tcount > ttable. Hence, the result indicated that implementing the OTPS learning model optimized using LMS could improve the student learning outcomes in calculus.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-ID JA X-NONE <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" Priority="47" Name="Grid Ta